Monoclonal gammopathy evolving into sytemic amyloidosis with cardiac involvement. A case report - Valenzuela-Rodríguez, Germán (2025)
We report a case of systemic light chain amyloidosis with cardiac involvement, preceded by a monoclonal IgG lambda gammopathy. The clinical diagnosis was based on signs of heart failure, elevated biomarkers, and imaging findings. The diagnosis was confirmed by elevated light chains in the blood and urine, and the presence of amyloid deposits in the periumbilical fat biopsy and in different segments of the digestive tract. Treatment with daratumumab plus bortezomib plus dexamethasone was initiated, and autologous hematopoietic stem cell therapy was administered 22 months after diagnosis, with a favorable clinical outcome.